HUBUNGAN KINERJA GURU DENGAN PRESTASI BELAJAR SISWA SDN GUGUS V KECAMATAN GUNUNG SARI TAHUN 2015/2016 - Putu Sthiti Waisnawa Putri; Lalu M. Tauhid; Heri hadi Saputra (Indonesian Journal of Elementary and Childhood Education, 2020)
The purpose of this research is to know the describe of teacher’s performance, the describe of student’s achievement and the correlation between the teacher’s performance and the student’s achievement Elementary School Group 5 Gunung Sari Subdistrict in year of 2015/2016. The research is based from the issues that the teacher’s performance is allegedly correlated to the student’s study achievement. This research is by using Correlative Descriptive Approach. The technique used to retrieve data is by using the questionnaire method and documentation method. The sample of this research is 80 students that is choose by using Stratified Proportional Random Sampling method to Students Grade IV, V, and VI of Elementary School Gugus V Gunung Sari subdistrict. The result of this research show that the average value of teacher’s performanceis 23,27 (very high). Besides the average value of student’s achievement is 77,42 (middle high). There is a positive and significant correlation between the teacher’s performance and the student’s achievement that showed by koefisien korelasi (r) among the variable of teacher’s performance and the student’s study achievement is 0,479 based on significance rate on 5% with the rCount > rTable (0,479 > 0,220) which is means that variable of teacher’s performance and variable of student’s achievement is significantly correlated.